Penerapan Akuntansi Lingkungan Terhadap Pengelolaan Limbah Pabrik Pakan Ternak PT Universal Agri Bisnisindo - Billy Josiah Aruan (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This research aims to determine the implementation of environmental accounting in animal feed mills to the management of waste at UAB animal feed mill. The method used in this research is qualitative method with an interpretive paradigm and ethnometodology approach. The technique of data analysis used at the time of data collection in the form of interviews, observation, and documentation to key informants and supporting informants. Result of this research are that UAB animal feed mill has prevented the problem of waste properly. Have an IPAL machine that serves to reduce the occurrence of waste that comes out of the production process. UAB animal feed mill has implemented environmental accounting by indetifying costs, recognizing costs, measuring costs, presenting costs, and disclosing costs which are the steps of accounting treatment for the management of factory waste. This company indetifies costs and recognizes environmental costs incurred as operating costs using the accrual basis method. Measurement using monetary units, by determining the amount of costs to be paid. This company presents environmental costs together with costs related to waste management. The presentation and disclosure are carried out together as sub-operational costs in the account of general and administrative costs. Keywords: Enviromental accounting, Animal feed mill , waste management, UAB animal feed mill